Ecological Responses of Core Phytoplankton by Latitudinal Differences in the Arctic Ocean in Late Summer Revealed by 18S rDNA Metabarcoding - Joo, Hyoung Min; Kim, Kang Eun; Park, Joon Sang; Kim, Hyun-Jung; Yang, Eun Jin; Lee, Taek-Kyun; Cho, Kyoung-Ho; Jung, Jinyoung; Lee, Youngju; Kang, Sung-Ho; Jung, Seung Won (Frontiers in Marine Science, 2022)
Limited information is available regarding the phytoplankton communities in the Arctic Ocean, especially in the Chukchi Sea. We conducted research cruises in the Arctic Ocean in the late summers of 2015, 2016, 2018, and 2019, and used 18S ribosomal DNA metabarcoding to examine the dynamic changes in core phytoplankton. Environmental factors were divided into three Groups: “surface layers in low latitude”, “subsurface chlorophyll maximum layers in low latitude”, and “high latitude.” The phytoplankton community was divided into two Groups. One Group, “the phytoplankton community in lower latitudes affected by the Pacific Influx “, comprised Dinophyta (56.33%), Bacillariophyta (22.28%), and Chlorophyta (20.77%), while the other Group, “the phytoplankton community in higher latitudes affected by the Arctic Sea “, comprised Dinophyta (57.51%), Bacillariophyta (10.71%), and Chlorophyta (27.57%). The common phytoplankton taxa in Group of lower latitudes included 33 operational taxonomic units (OTUs) (99.04%), while the other Group included nine OTUs (98.80%). In these groups, OTUs #005 (Heterocapsa rotundata), #001 (Micromonas pusilla), and #003 (Chaetoceros gelidus) were core OTUs (>5%). These core OTUs were significantly different between the two Groups; OTU #001 and #003 were distributed at high relative abundance and rapidly increased at higher latitudes. OTU #005 showed a relatively high abundance at lower latitudes. Analysis of the indicator species revealed that 34 OTUs in lower latitudes and only one OTU (#003) in higher latitudes were observed to have a strong value of >0.8. Our results indicate that core phytoplankton taxa and community structures by latitudinal differences are highly dependent on different water masses and show their dynamic ecological responses to extreme environmental conditions.